# Solve the equation 4a - 7 = 4(a - 2) + 1

### 6 Answers | Add Yours

The equation 4a - 7 = 4(a - 2) + 1 has to be solved.

4a - 7 = 4(a - 2) + 1

=> 4a - 7 = 4a - 8 + 1

=> 4a - 7 = 4a - 7

=> -7 = -7

This is true for any value of a.

**The equation 4a - 7 = 4(a - 2) + 1 is true no matter what value is given to a.**

4a - 7 = 4(a - 2) + 1

4a=4a-8+1+7

4a-7=4a-7

4a-7=4(a-2)+1

Open the bracket

4a-7=4a-8+1

Collect the like terms

4a-4a=-8+1+7

O=0

Ans=0

4a-7=4{a-2}+1

4a-7=4a-8+1

4a-4a=-8+7+1

0=0

hence,ans=0

4a - 7 = 4(a - 2) + 1 the first step is to distribute the 4

4a-7=4a-8+1

4a-7=4a-7 now combine the terms by taking away and adding

4a-4a=7-7 0=0

so the answer is 0

4a-7=4(a-2)+1

4a-7=4a-8+1

4a-7=4a-7

4a-7+4a=4a-7-4a

-7=-7

-7+7=-7+7

0=0